Two years of approved digital health applications in Germany – Perspectives and experiences of general practitioners with an affinity for their use - Julian Wangler; Michael Jansky (European Journal of General Practice, 2023)
AbstractBackground Since 2020, physicians in Germany can prescribe approved digital health applications (DHAs) with the costs covered by the health system. There has so far been a lack of studies on attitudes and experiences amongst GPs in using DHAs.Objectives The aim was to elucidate the experiences and observations of GPs that have used DHAs in health care and to examine the conditions necessary for DHAs to gain a foothold in primary care according to the GPs.Methods In 2022, 96 qualitative semi-standardised interviews were conducted with German GPs with experience in prescribing DHAs. The GPs were all organised in digitalisation-oriented physicians’ associations. Fifty-four interviews were carried out in person and 42 by phone. The data were analysed according to qualitative content analysis.Results Unlike health apps, the interviewees saw DHAs as reliable tools for enhancing the relationship between GPs and their patients. They saw the DHAs they had been prescribing as useful and reported various benefits, including improvements in compliance, mobility, information for patients and weight reduction. The physicians also saw room for further improvement (usability, gamification, training, information sources). Interviewees saw the inclusion of DHAs in evidence-based guidelines as a major step forward.Conclusion The interviewees rated DHAs favourably regarding healthcare potential and as safer and more reliable than conventional health apps. Many saw benefits to healthcare from using such applications. From the interviewees’ point of view, DHAs can be integrated more effectively into patient care.